A late Holocene record of solar-forced atmospheric blocking variability over Northern Europe inferred from varved lake sediments of Lake Kuninkaisenlampi. (15th December 2016) - Saarni, Saija; Muschitiello, Francesco; Weege, Stefanie; Brauer, Achim; Saarinen, Timo
Abstract: This study presents a new varved lake sediment sequence from Lake Kuninkaisenlampi, Eastern Finland. The record is constituted by alternations of clastic and biogenic laminae and provides a precise chronology extending back to 3607 ± 94 varve yrs. BP. The seasonality of the boreal climatic zone, with cold winters and mild summers, is reflected in the varve structure as a succession of three laminae from bottom to top, (i) a coarse to fine-grained detrital lamina marked by detrital catchment material transported by spring floods; (ii) a biogenic lamina with diatoms, plant and insect remnants reflecting biological productivity during the season of lake productivity; and (iii) a very fine amorphous organic lamina deposited during the winter stratification. The thickness of the detrital lamina in the lake reflects changes in the rate of spring snow melt in the catchment and is, therefore, considered a proxy for winter conditions. Hence, the record allows reconstructing local climate and environmental conditions on inter-annual to the multi-centennial timescales. We find that minerogenic accumulation reflected in the detrital lamina exhibits a high multi-decadal to centennial-scale spectral coherency with proxies for solar activity, such as Δ 14 C, and Total Solar Irradiance, suggesting a strong link between solar variability and sediment transport to the lake basin. Increased catchment erosion is observed during periods of low solar activity, which we ascribe to the development of more frequent atmospheric winter blocking circulation induced by solar-forced changes in the stratosphere. We suggest that soil frost in the catchment of Lake Kuninkaisenlampi related to more frequent winter blocking led to increased surface run-off and ultimately to increased catchment erosion during spring. We conclude that, during the past ca 3600 years, solar forcing may have modulated multi-decadal to centennial variations in sedimentation regimes in lakes from Eastern Finland and potentially in other North European lakes. Highlights: A new clastic-organic varve record from Eastern Finland covers the last 3600 years. Record suggests that increased catchment erosion occurs during low solar activity. The atmospheric blocking is suggested to explain the link.